2012
DOI: 10.1007/s13142-012-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral health referrals and treatment initiation rates in integrated primary care: a Collaborative Care Research Network study

Abstract: Although the benefits of integrating behavioral health (BH) services into primary care are well established (World Health Organization and World Organization of Family Doctors, 2012; Chiles et al. in Clin Psychol-Sci Pr 6:204-220, 1999; Cummings 1997; O'Donohue et al. 2003; Olfson et al. in Health Aff 18:79-93, 1999; Katon et al. in Ann Intern Med 124:917-925, 2001; Simon et al. in Arch Gen Psychiatry 52:850-856, 1995; Anderson et al. in Diabetes Care 24:1069-1078, 2001; Ciechanowski et al. in Arch Intern Med … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
(15 reference statements)
0
40
0
Order By: Relevance
“…26,28,30,42,43 Previous studies have found that colocation improved access to mental health care 30,44 and engagement with mental health care providers 31,45 and improved patient satisfaction and outcomes. 46,47 We hypothesized that colocation would result in increased diagnosis and prescribing by bringing expertise with these conditions to the practice and potentially drawing additional children needing these services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,28,30,42,43 Previous studies have found that colocation improved access to mental health care 30,44 and engagement with mental health care providers 31,45 and improved patient satisfaction and outcomes. 46,47 We hypothesized that colocation would result in increased diagnosis and prescribing by bringing expertise with these conditions to the practice and potentially drawing additional children needing these services.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several practice-level characteristics might affect the primary care delivery of mental health services. In response to family difficulties in accessing mental health specialists, 24,25 primary care practices increasingly include colocated mental health providers, [26][27][28][29][30] a model that may improve access, identification, and treatment. 26,31 Second, practices with higher numbers of patients in foster care may manage more mental health care owing to prevalent psychotropic medication use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of referral by health care professionals may contribute to long delays between the beginning of COs' difficulties and their seeking help through Al-Anon (Timko et al, in press). Patients with SUDs who receive enhanced referrals to 12-step groups by health care providers participate more in meetings and have better outcomes (Timko, DeBenedetti, & Billow, 2006; Timko, Sutkowi, Cronkite, Makin-Byrd, & Moos, 2011), and individuals referred by health care providers to behavioral health services follow through with referrals at high rates (over 80%) (Auxier et al, 2012; Healey et al, 2013). Overall, individuals are more likely to become engaged in Al-Anon when attendance is recommended by health care professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to 2010, state and national leaders began to explore integrated care as a new model for behavioral and primary care services through special tasks forces on workforce, reimbursement, and population-based service needs, some of which included one of the authors. State policy makers and leading local health insurers started to support changes in traditional behavioral health programs at this time, modestly supporting behavioral health interventions in adult primary care, obstetrics, neurology, and gastroenterology 7,21,22 . These changes allowed primary care services to bill directly for behavioral health services using traditional psychotherapy codes and reduced prior approval requirements for these services.…”
Section: Introductionmentioning
confidence: 99%